Intradialitik gemodinamik beqarorlikning patogenezi (CARDIOLOGY OF UZBEKISTAN, 2024)
Background: The study explores mechanisms of intradialytic hemodynamic instability, which remains a significant challenge in the management of chronic kidney disease patients undergoing hemodialysis. Understanding the factors contributing to this condition is crucial for enhancing patient outcomes. Objective: To review and analyze the primary pathophysiological mechanisms leading to intradialytic hemodynamic instability. Material and Methods: The review synthesizes data from recent studies and clinical trials focused on hemodynamic changes during hemodialysis. The analysis includes factors like plasma volume reduction, myocardial contractility, and systemic perfusion. Results: The main mechanisms of intradialytic hemodynamic instability involve decreased plasma volume, reduced venous return, lower left ventricular preload and contractility, and diminished stroke and minute volumes. Secondary contributing factors include chronotropic insufficiency, pathological myocardial remodeling, and systemic and regional perfusion deficits affecting abdominal, cerebral, and coronary circulation. Conclusion: Comprehensive understanding of the pathogenesis of intradialytic hemodynamic instability highlights the importance of targeted therapeutic interventions to mitigate cardiovascular risks and improve patient quality of life.